HUBUNGAN KAUSALITAS ANTARA NILAI TUKAR MATA UANG DAN INDEKS HARGA SAHAM DI PASAR MODAL INDONESIA - Sulistyandari, Sulistyandari (Performance, 2011)
This paper examines the relationship between exchange rates and stock prices indexs in the emerging financial market of Indonesia using daily data over a four-year period from January, 2002 to December, 2005. The motivation is to establish the causal linkages between leading prices in the foreign exchange market and the stock market in Indonesian market; the linkages have implication for the ongoing attempts to develop stock markets simultaneously with a policy shift towards independently floating exchange rates Using the Granger concept of causality (1969), cointegration technique and standard Error Correction Model (ECM), show that consistent with portfolio approach to exchange rate determination, it is argued that there is a negative short run and long run causality from stock prices to exchange rates (unidirectional causality from stock prices to exchange rates). A change in stock prices have an impact on exchange rate for composite indexs (IHSG) and also for sectoral indexs The result have implication that the development on the stock market are important to economics development, increasing on the stock market performance become an indicator of a good macro economic condition and appreciate the domestic currency.